RATIONAL CHOICE THEORY SEBAGAI PENENTU MOTIF TINDAK PIDANA PENGEDARAN NARKOTIKA MELALUI MEDIA SOSIAL DI SIDOARJO - Suwandi, Nur Ainy Amira Puspitaning; Hermono, Budi (Universitas Negeri Surabaya, 2018)
The core issue in this research is the emergence of a new method of drug distribution through social media platforms such as Facebook and Instagram. This study focuses on the distribution of narcotics through social media within the jurisdiction of the Sidoarjo City Police Resort and examines it using the rational choice theory. This gives rise to the following problems: 1. What motives do drug dealers have for distributing drugs through social media, as viewed from the perspective of rational choice theory? 2. What actions do the police take against the criminal act of drug distribution through social media? The purpose of this research is to identify and analyze the motives of drug dealers in distributing through social media, as well as the actions taken by the police against the criminal act of drug distribution through social media. The research methodology used is qualitative empirical legal research. The study was conducted at the Sidoarjo Class IIA Penitentiary and the Sidoarjo City Police Resort. The research method involves interviews as primary legal data and legislation as secondary legal data. The results of this research are as follows: 1. The distribution of narcotics through social media has benefits and costs. In this study, the benefits outweigh the constraints or losses incurred. 2. The actions taken by the police against the distribution of narcotics through social media. Individual may consciously commit a criminal act due to the presence of rational choice theory, whereby a person considers the benefits and losses they may incur.